Feasibility Test and Student Response to Interactive E-Modules on Recreational Fashion Design at Vocational High Schools - Mawaddah, Rizky Dinda Aulya; Wahyuningsih, Sri Endah (Universitas Negeri Semarang, 2026)
This research was motivated by the limited availability of interactive teaching materials for Fashion Design and Production courses in vocational schools, particularly for recreational fashion design, which requires a high level of visual and procedural understanding. The purpose of this study was to develop and test the feasibility of an interactive e-module based on Heyzine Flipbook and to determine students' responses to it. The research method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects involved three subject matter experts, three media experts, and 34 11th grade Fashion Design students at SMK Negeri 6 Semarang. The results showed that the e-module was highly feasible based on subject matter expert validation with a percentage of 91.67% and media expert validation of 96.05%. The practicality test using a student response instrument showed an average achievement of 83.71% with a very positive criterion. The research findings indicate that the integration of interactive features in e-modules is able to visualize complex material in a concrete manner, thereby increasing student learning independence. The conclusion of this study is that HeyzineFlipbook-based e-modules are feasible and effective for use as an innovation in digital learning media to support the independent curriculum in vocational education.